2018
DOI: 10.3390/ijerph15091998
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Health Care-Seeking Delay among Tuberculosis Patients in Rural Area of Central China

Abstract: Background The prevalence of tuberculosis (TB) in low and middle-income countries is a significant public health and social concern. TB is a common infectious disease caused by the Mycobacterium tuberculosis infection, which has a widespread infection rate. Health care-seeking delay maybe one of the most important neglected risk factors for the spread of TB. Objectives The aim of this study was to understand the situation of health care-seeking delay among rural tuberculosis patients in Hubei Province, and exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
4
11
1
Order By: Relevance
“…15 16 That employment could play a role in care-seeking has also been indicated by a previous study in South India, where ‘pressure of work’ was associated with delays 19 ; another study in Chennai had found that 31% of employed patients with TB, versus just 24% of non-employed patients, had taken action more than 30 days after symptom onset. 15 Our results may not all generalise to other geographies; for example, studies in several African countries 10 11 13 and China 12 did find that TB disease knowledge predicted care-seeking delays.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…15 16 That employment could play a role in care-seeking has also been indicated by a previous study in South India, where ‘pressure of work’ was associated with delays 19 ; another study in Chennai had found that 31% of employed patients with TB, versus just 24% of non-employed patients, had taken action more than 30 days after symptom onset. 15 Our results may not all generalise to other geographies; for example, studies in several African countries 10 11 13 and China 12 did find that TB disease knowledge predicted care-seeking delays.…”
Section: Discussionmentioning
confidence: 74%
“…8 Many studies have been conducted both globally [9][10][11][12][13][14] and in the Indian context [15][16][17][18][19][20] to better understand TB patient care-seeking pathways. These studies find a number of factors to be commonly associated with delayed care-seeking, including lack of knowledge about TB, [10][11][12][13] being a woman, 11 14 20 lack of education, 11 living far from health facilities, 11 12 15 20 visiting informal care providers, 11 13 low income in Africa and Asia, 14 20 high income in South India, 16 age, 9 10 13 19 and tobacco and alcohol use. 16 21-25 Although existing research provides some insight into what drives people to seek care for their TB symptoms, these studies often only focus on a limited set of potential drivers, many of which are demographic variables.…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…Hubei province can be classified as having a moderate economic and medical development in central China. It is a very representative of economy, politics, culture and geography in China 25 . Meanwhile, the ageing of the elderly population in Hubei province is extremely severe, higher than the national average (Table 1), and the aging phenomenon of the rural population in Hubei province is more prominent than that of the urban population.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals with possible TB symptoms who do not seek medical care will miss the opportunity for early detection of TB, leading to delayed treatment and poor prognoses. [23][24][25] In addition, unwillingness to seek medical care may increase the potential risk of transmission and will have a negative impact on their families and society. 26 Our findings showed that the main reason for being unwilling to seek medical care for TB was 'long treatment cycle and heavy economic burden'.…”
Section: Discussionmentioning
confidence: 99%